2018
DOI: 10.1097/wnr.0000000000001106
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic atrophy and dysfunction in patients with mild-to-moderate traumatic diffuse axonal injury

Abstract: Disrupted white matter structure has been established in patients with diffuse axonal injury (DAI), but morphological changes in gray matter and local intrinsic activity in the short and midterm (before 6 months) have not been documented in DAI patients. We hypothesized that regionally selective atrophy observed in deep gray matter in the short-term and mid-term periods in patients with mild-to-moderate DAI, local atrophy, and/or dysfunction would be related to clinical characteristics. We evaluated the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Previous studies, including our own work, have reported differences compared to controls in thalamic and corpus callosum volumes in disorders that affect the white matter, including traumatic brain injury and multiple sclerosis. 5,[14][15][16] Animal studies of head trauma indicate that blows to the head can result in physical injury to axons. 17 Because the thalamus has abundant afferent and efferent fibers, the progressive loss of volume seen may reflect Wallerian degeneration of the axons with subsequent neuronal dropout, though other mechanisms that may reduce thalamic volume are also possible.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, including our own work, have reported differences compared to controls in thalamic and corpus callosum volumes in disorders that affect the white matter, including traumatic brain injury and multiple sclerosis. 5,[14][15][16] Animal studies of head trauma indicate that blows to the head can result in physical injury to axons. 17 Because the thalamus has abundant afferent and efferent fibers, the progressive loss of volume seen may reflect Wallerian degeneration of the axons with subsequent neuronal dropout, though other mechanisms that may reduce thalamic volume are also possible.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing numbers of studies have revealed compensatory activation (7) or engagement (8) in working memory performance task, disrupted regional (9) and long-distance connectivity (10,11), and even network dysconnectivity (12). However, these studies relied on the assumption of the 'static' temporal strength or inter-region relationship in temporal pattern, neglecting to investigate the dynamic brain alterations or time-varying of the blood oxygen level dependent (BOLD) signal in resting-state scanning (13).…”
mentioning
confidence: 99%
“…The thalamus, while traditionally considered a relay station for the cortex, has an active role in many higher‐level cognitive processes including memory, attention, and processing speed, and is specifically implicated in cognitive effects of aging (Fama & Sullivan, 2015). Thalamic atrophy has been reported in the short term after mild‐to‐moderate TBI, with implications for post‐traumatic symptoms (Wu et al, 2018) and in mild TBI, thalamic damage accounts for many neurocognitive impairments (Grossman & Inglese, 2016). The ubiquity and unique trajectory of thalamic atrophy positions this structure as a promising biomarker for injury severity and prognosis; yet, much work is needed to relate thalamic atrophy to its connected structures (e.g., anterior and posterior cerebral cortex) and examine its role in functional outcomes following injury.…”
Section: Discussionmentioning
confidence: 99%